(untitled) (Sociología y tecnociencia, 2026)
This study analyzes mental health and its relationship with digital media use among the adolescent population in contexts with specific challenges, such as that experienced on the island of La Palma (Canary Islands) following the pandemic and a volcanic eruption. Results corroborate that Compulsive Internet Use (CIUS) is significantly associated with higher levels of anxiety, emotional distress, sleep problems, and lower self-esteem, also confirming a significantly higher prevalence in females across all of them. Although CIUS prevalence does not differ between zones, a moderating effect trending towards significance on anxiety is observed: with higher CIUS risk, adolescents in the affected zone report lower anxiety levels. Although moderation was not significant for other indicators, the affected zone generally presents lower emotional distress in females and males, as well as higher self-esteem and fewer sleep difficulties in females. These findings suggest that specific post-disaster contextual factors might have fostered better emotional management among adolescents in the affected zone, partially mitigating the impact that problematic digital media use has on mental health. The need for preventive interventions to alleviate the impact of digital media on mental health from a gender perspective, contextualized to geographical particularities, is emphasized.